Distinct relationships of amyloid-beta and tau deposition to cerebral glucose metabolic networks in Alzheimer's disease. (19th January 2020) - Sun, Xi; Nie, Binbin; Zhao, Shujun; Ai, Lin; Chen, Qian; Zhang, Tianhao; Pan, Tingting; Wang, Luying; Yin, Xiaolong; Zhang, Wei; Shan, Baoci; Liu, Hua; et al.
Highlights: A multimodal PET study of AD combining 18 F-AV-45, 18 F-AV-1451 and 18 F-FDG. Relationships of amyloid-beta and tau to glucose metabolic networks. Positive relation of amyloid-beta while negative of tau to metabolic networks. Independent contributions of amyloid-beta and tau in AD. Abstract: Extracellular accumulation of amyloid-beta peptides and intracellular neurofibrillary tangles (NFTs) of hyperphosphorylated tau proteins are the two cardinally pathological hallmarks of Alzheimer's disease (AD). However, their exact roles in the mechanisms of AD progression are not well established. Given that AD is a disconnection syndrome and hypometabolism is one of its most important neurodegenerative indicators, we hypothesized amyloid-beta and tau burden may disturb the glucose metabolic network of AD. Here we investigated the relationship of these two factors to regional metabolic network properties using multimodal positron emission tomography (PET) imaging data. Participants included six groups covering from cognitively normal controls, patients with early cognitive impairment (MCI), late MCI, mild AD, moderate AD to severe AD who underwent amyloid-beta PET, tau PET and fluorodeoxyglucose (FDG) PET. Glucose metabolic network of each group was constructed and relations of amyloid-beta and tau to regional metabolic network measurements were investigated. Results revealed distinct associations of these two hallmarks to metabolic networks: amyloid-beta were positively related to metabolic network measurements at relative early phases of AD, while tau burden showed a negative relationship at late phase of AD. These results supported the notion that amyloid-beta and tau accumulation may contribute independently to mechanisms of AD. Furthermore, these findings might also provide connectivity evidence for the speculation that amyloid-beta deposition is protective to neuronal activity.